PENGARUH KEBIJAKAN DIVIDEN DAN KEPUTUSAN INVESTASI TERHADAP HARGA SAHAM PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DIBURSA EFEK INDONESIA PERIODE 2009-2014 - Fatkur Rahmawati; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to analyze the factors that influence dividend policy and investment decisions on stock prices. Population in this study is a transport company listed dibursa securities indonesia which amounted to 7 companies with the period 2009-2014. Data collection techniques using annual financial reports faithfully year.The results of data analysis or regression results show that simultaneously dividend policy and investment decisions significantly influence the stock price.keywords: Effect of dividend policy and investment decisions on stock prices